Investigating barriers to genetic counseling and germline mutation testing in women with suspected hereditary breast and ovarian cancer syndrome and Lynch syndrome. Issue 5 (May 2018) - Shaw, Josephine; Bulsara, Caroline; Cohen, Paul A.; Gryta, Madeleine; Nichols, Cassandra B.; Schofield, Lyn; O'Sullivan, Sarah; Pachter, Nicholas; Hardcastle, Sarah J.
Highlights: A qualitative study of why gynecologic cancer patients decline genetic testing. Themes identified included lack of importance and level of information received. Timing of referral; fear and perceptions of counseling were also identified. Most participants did not appreciate the potential benefits of testing. Abstract: Objective: The aim of the current study was to explore barriers to genetic counseling and testing in women with gynecological cancers deemed at significant risk of carrying a germline mutation. Methods: A qualitative study using semi-structured interviews and inductively analysed thematically. Eight patients with ovarian or endometrial cancer participated in individual semi-structured telephone interviews that assessed motivation for genetic counseling and testing, perceived benefits and barriers, timing of the approach, perceptions of the referral process to genetic services and locus of control in relation to cancer and health. Results: Analysis of the interview transcripts revealed five themes relating to perceptions of genetic counseling and testing: Lack of importance; Level of information received; Timing of referral processes; Fear and anxiety; Resistance to and perceptions of counseling . Conclusions: Participants had a limited understanding of hereditary cancer syndromes and did not appreciate the benefits of genetic testing. A consistent approach at the time of referral to genetic services is needed to ensure that the level and format of information is appropriate for patients. Practice implications: The rationale for genetic testing needs to be better explained to patients and the timing of referral should be based both on treatment priorities and patient preferences.